ANALISA KOMPOSISI MINYAK ATSIRI KULIT JERUK MANIS HASIL EKSTRAKSI METODE MICROWAVE HYDRODIFFUSION AND GRAVITY DENGAN GC-MS - Ayu Chandra Kartika Fitri; Wahyu Diah Proborini (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2018)
This study aims to determine percent yield and chemical composition of volatile oil from citrus peel that extracted by using Microwave Hydrodiffusion and Gravity method. Chemical composition was analyzed using Gas-Chromatography method. Based on gas chromatography analysis (GC) obtained 9 peaks with different retention time according to the type of compound that was analyzed. The highest peak comes with retention time of 8.440 with wide area 22623980 (97,78%) and height 7241224 (96,70%). Height is the distance from the base line to the maximum peak usually in mm, while the area is the area under the peak, and indicates the abundance of a component. Retention time is the time interval required by the solute (component) to get out of the column and reach the detector.